2005
DOI: 10.1104/pp.105.069146
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Inorganic Carbon Limitation in Synechococcus PCC7942 Is Correlated with the Size of the Internal Inorganic Carbon Pool and Involves Oxygen

Abstract: Freshwater cyanobacteria are subjected to large seasonal fluctuations in the availability of nutrients, including inorganic carbon (Ci). We are interested in the regulation of the CO 2 -concentrating mechanism (CCM) in the model freshwater cyanobacterium Synechococcus sp. strain PCC7942 in response to Ci limitation; however, the nature of Ci sensing is poorly understood. We monitored the expression of high-affinity Ci-transporter genes and the corresponding induction of a high-affinity CCM in Ci-limited wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 63 publications
5
85
0
Order By: Relevance
“…The acclimation to LC increased the affinity toward bicarbonate approximately 4-fold in both cultures (wildtype K 1/2 = 35.5 6 6.4 mM, mutant MP2 K 1/2 = 46.2 6 19.6 mM). Previous studies revealed similar C i affinities for HC cells (approximately 150 mM) that increased up to 10-fold during the first few hours after the shift from HC to LC conditions in Synechococcus 7942 (Woodger et al, 2003(Woodger et al, , 2005.…”
Section: Physiological Characterizationmentioning
confidence: 94%
See 1 more Smart Citation
“…The acclimation to LC increased the affinity toward bicarbonate approximately 4-fold in both cultures (wildtype K 1/2 = 35.5 6 6.4 mM, mutant MP2 K 1/2 = 46.2 6 19.6 mM). Previous studies revealed similar C i affinities for HC cells (approximately 150 mM) that increased up to 10-fold during the first few hours after the shift from HC to LC conditions in Synechococcus 7942 (Woodger et al, 2003(Woodger et al, , 2005.…”
Section: Physiological Characterizationmentioning
confidence: 94%
“…The metabolites of these pathways changed similarly in LC-shifted wild-type cells as well as PII mutant cells. Whether instead of 2OG another metabolite specifically induced by LC conditions, such as 2PG (Marcus et al, 1983;Eisenhut et al, 2008a;Kaplan et al, 2008;Nishimura et al, 2008), or another internal signal, such as the internal pool of C i , as suggested by Woodger et al (2005), serves as the signal to induce the LC-specific acclimation processes needs additional investigation. The differences in the metabolome between the wild type and the MP2 mutant can be expected to be, to a large extent, the result of changes in the transcription of genes for specific enzymes of the central C and N metabolism.…”
Section: Comparison Of the Metabolome Of The Wild Type And Pii Mutantmentioning
confidence: 99%
“…Mutants-Tagged or untagged versions of CcmM where expressed from various shuttle vectors (detailed below) and expressed in either WT Synechococcus PCC7942 cells or in the ⌬ccmM markerless deletion mutant (17).…”
Section: Expression Of N-and C-terminally Tagged His 6 Ccmmmentioning
confidence: 99%
“…It is therefore probable that both forms are translated from the same gene transcript and that each form has specific functions within the carboxysome shell. Here we present a novel gene complementation approach that utilizes the carboxysomeless Synechococcus PCC7942 mutant ⌬ccmM (16,17) and wild type (WT) cells to investigate the binding partners of CcmM within carboxysomes. Plasmid DNA constructs containing chimeric forms of ccmM, coding for His 6 tags at both the N and C termini of CcmM, were introduced into both WT and ⌬ccmM cell types.…”
mentioning
confidence: 99%
“…CcmM mutants do not contain carboxysomes and have the hcr phenotype [20,[58][59][60], indicating that the protein is important for carboxysome structure and/or biogenesis.…”
Section: Ccmmmentioning
confidence: 99%